2015
DOI: 10.1109/tbme.2015.2407835
|View full text |Cite
|
Sign up to set email alerts
|

Denoising of Contrast-Enhanced Ultrasound Cine Sequences Based on a Multiplicative Model

Abstract: Phantom experiments showed improved SNR, using wavelet denoising over a wide range of UCA concentrations (MicroMarker, 0.001-1%). In the in vivo tests, improved noise removal was achieved, reflected by a significantly lower coefficient of variation in homogeneous vascular regions (p < 0.01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…To estimate the local time-intensity curves (TIC) in the DCEUS movies, temporal wavelet denoising was applied to each pixel in the scans (13). From the denoised scans, three different perfusion parameters were estimated, producing high-resolution parametric maps of the tumors: peak enhancement, the difference between maximum amplitude, and the baseline intensity of the wash-in curve, used as an indication of the tumor blood volume; wash-in rate, the maximum slope of the curve, used as an indication of blood flow rate; and area under the curve, the integrated difference between the intensity value and its baseline.…”
Section: Image Analysismentioning
confidence: 99%
“…To estimate the local time-intensity curves (TIC) in the DCEUS movies, temporal wavelet denoising was applied to each pixel in the scans (13). From the denoised scans, three different perfusion parameters were estimated, producing high-resolution parametric maps of the tumors: peak enhancement, the difference between maximum amplitude, and the baseline intensity of the wash-in curve, used as an indication of the tumor blood volume; wash-in rate, the maximum slope of the curve, used as an indication of blood flow rate; and area under the curve, the integrated difference between the intensity value and its baseline.…”
Section: Image Analysismentioning
confidence: 99%
“…However, these results must be considered within the context of the curve‐fitting performed in this study. A number of groups have shown that the multiplicative nature of speckle noise in CEUS cine loops necessitates the use of MLE fitting of indicator‐dilution curve models instead of a nonlinear least squares method. There is a possibility that switching to MLE for LDRW fitting would result in improved discrimination of treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important in the early wash‐in phases of contrast‐enhancement. Addressing this would require a change in the parameterized distribution from an exponential to a K distribution, but the gain in model accuracy may be outweighed by decrease in parameter estimation stability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fitting single-pixel TICs is especially challenging because of lower signal-to-noise ratios. Next to standard least-squares approaches, several authors have introduced maximum-likelihood approaches that account for the statistics of arrival times (measured TIC) as well as noise, which has non-stationary characteristics depending on the UCA concentration levels (Barrois et al 2013;Kuenen et al 2013a;Bar-Zion et al 2015). In Figure 6 is an example of a parametric map of local dispersion obtained in prostate tissue.…”
Section: Temporal Analysismentioning
confidence: 99%